Human stefin B: from its structure, folding, and aggregation to its function in health and disease - Žerovnik, Eva (Frontiers in Molecular Neuroscience, 2022)
Mutations in the gene for human stefin B (cystatin B) cause progressive myoclonic epilepsy type 1 (EPM1), a neurodegenerative disorder. The most common change is dodecamer repeats in the promoter region of the gene, though missense and frameshift mutations also appear. Human stefin B primarily acts as a cysteine cathepsin inhibitor, and it also exhibits alternative functions. It plays a protective role against oxidative stress, likely via reducing mitochondrial damage and thus generating fewer mitochondrial reactive oxygen species (ROS). Accordingly, lack of stefin B results in increased inflammation and NLRP3 inflammasome activation, producing more ROS. The protein is cytosolic but also has an important role in the nucleus, where it prevents cleavage of the N terminal part of histone 3 by inhibiting cathepsins L and B and thus regulates transcription and cell cycle. Furthermore, it has been shown that stefin B is oligomeric in cells and that it has a specific role in the physiology of the synapse and in vesicular transport. On the basis of my research team’s data on the structure, folding, and aggregation of stefin B, we have proposed that it might regulate proteostasis, possessing a chaperone-like function. In this review, I synthesize these observations and derive some conclusions on possible sources of EPM1 pathology. The interaction partners of stefin B and other gene mutations leading to EPM1-like pathology are discussed and common pathways are pinpointed.